Prekmurski jezik med knjižno normo in narečjem - Jesenšek, Marko (University of Maribor Press, 2018)
The Language of Prekmurje Between Literary Norm and Dialect. The discussions are supplementing my thoughts on Prekmurian language in the previous monograph Poglavja iz zgodovine prekmurskega knjižnega jezika (2013); therefore, I make a distinction between (former) literary norm and (modern-day) dialect. The story of the origins, geographical context, development and decline of Prekmurian literary language and its transition into dialect form (due to the formation of a uniform Slovene literary language) is thus getting its final lines and enables a different view on the development of Slovene language, emphasizing the dual development in the central and eastern Slovene language area. Until the formation of “Newslovene”, these were determined by literary Carniolan and Prekmurian. I emphasise, in particular, new insights on Prekmurian, which enable the understanding of its literary (in the past) and dialectal (present) characteristics.